Influence of different species of Penicillium and their culture filtrates on seed germination and seedling growth of sorghum - Vankudoth, Koteswara Rao (Journal of Biochemical Technology, 2014)
The present investigations influence of Penicillium species and their culture filtrates on the seed germination and seedling growth of sorghum was studied. Culture filtrate of P. nordicum, P. verrucosum, P. chrysogenum, P. commune, P. citrinum, P.camemberti and P. digitatum were comparatively more toxic and significantly inhibited the seed germination and seedling growth varied with the species. However, pathogenicity of different inoculum of Penicillium species also exhibited varying seedling growth inhibition with P. citrinum, P. chrysogenum, P. commune, P. italicum, P. verrucosum and P. expansum assayed by water agar method. A significant phytotoxicity of these species inhibited coleoptile 32-70%, radicle 10-87% and leaf growth 20-86% with correlation coefficient 0.65, 0.67 and 0.79%, and were observed respectively. In-vitro mycotoxin production was assayed by culture filtrates of major mycotoxigenic strains revealed production of ochratoxin A (OTA), cyclopiazonic acid (CPA), rubratoxin B (RTB), griseofulvin (GRI), citrinin (CIT), patulin (PAT), penitrem A (PENA) and mycophenolic acid (MPA) screened by TLC/HPLC. Toxicity of species of Penicillium on seed germination, coleoptile, radicle, and leaf elongation inhibition may be attributed to the toxin-chemotypes produced by the species of Penicillium. However, even non-toxigenic strains of Penicillium also caused mild inhibition which may be attributed to the presence of other toxin-chemotypes.